La participación social en la reforma educativa en México 2012-2018 - Zurita Rivera, Ursula (Universidad de Costa Rica, 2020)
This essay examines how participation in schools was formulated in the educational reform undertaken in Mexico in 2012-2018. The intention is to know some of the main implications derived from its conception as a means to strengthen public, secular and free education, to ensure greater equity in access to quality education, to strengthen the management capacity of schools, establish the evaluation of the different components of the educational system and establish the professional teaching service that would converge in the implementation of the Project from the School to the Center and the New Educational Model. The central assumption is that the instrumental and pragmatic vision of participation was materialized in the schools through the operation of the Educational Reform Program, the Full-Time Schools Program, and the School Coexistence Program, quickly revealing the contradictions and limitations of the reform in this matter. The essay expresses that this conception preserved and strengthened the preeminence of the Mexican State in participatory processes, the production, and reproduction of a pseudo-social autonomy, as well as a subordinate, simulated, and passive participation, anchored in a vertical, bureaucratic and hierarchical logic of the Mexican educational system. Undermining the autonomous and independent expressions of actors such as parents and students who have historically been subordinated and made invisible despite their potential contribution to the expansion and deepening of the right to education, education for democratic life, and educational inclusion.